DEVELOPMENT TRENDS OF AUDITING ACTIVITIES IN UZBEKISTAN - Makhmudova R. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The article is devoted to the analysis of the current state of the audit services market in Uzbekistan. The latest changes in the legislative framework in the field of auditing are presented. The number of audit organizations and auditors, information about auditors, the dynamics of income of audit organizations and the distribution of subjects of audit activity by regions of the country are considered. The Law "On Auditing Activities" is analyzed. The conclusion is made about the main trends inherent in the Uzbek market of audit services.